2013
DOI: 10.1002/ca.22288
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the clavicle

Abstract: The clavicle has a complex osteologic structure that makes morphological analysis extremely difficult. A three-dimensional study was conducted to examine the anatomical variations and characteristics of the bone. Sixty-eight human cadaver clavicles were dissected, CAT-scanned, and reconstructed. An automated parameterization and correspondence shape analysis system was developed. A new length, designated as centerline (CL) length, was defined and measured. This length represents the true length of the clavicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 31 publications
0
17
2
Order By: Relevance
“…On the contrary, both sex and bilateral differences were found in adults, since numerous authors [ 10 – 13 ] reported clavicle length to be greater in men than in women. Albeit preponderance of researchers [ 4 , 8 , 10 , 11 , 13 – 16 ] reported the left clavicle to be consequently longer than the right one, only Mays et al [ 16 ] and Auerbach and Raxter [ 14 ] proved statistically significant right–left differences. We share the view of Mohsin et al [ 3 ] that in the fetus, the right and left clavicles develop symmetrically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, both sex and bilateral differences were found in adults, since numerous authors [ 10 – 13 ] reported clavicle length to be greater in men than in women. Albeit preponderance of researchers [ 4 , 8 , 10 , 11 , 13 – 16 ] reported the left clavicle to be consequently longer than the right one, only Mays et al [ 16 ] and Auerbach and Raxter [ 14 ] proved statistically significant right–left differences. We share the view of Mohsin et al [ 3 ] that in the fetus, the right and left clavicles develop symmetrically.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental anatomy and morphometric data provide clinicians of different specialties with relevant information [ 3 ]. In archeological studies, the clavicular model is germane to elucidate some mechanisms of evolution, while, in forensic medicine, it serves to determine sex, age, ethnic differences, and body posture [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To define the anatomical shape of the plate or to fix the fractured clavicle with intramedullary nails, a comprehensive understanding of the bony morphology is crucial. However, current morphologic studies focused on the western population [ 9 12 ]. There was no literature regarding the detailed anatomical data of the clavicle in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex and variable bony anatomy of the clavicle, an understanding of clavicular anatomy is paramount for optimal plate design and fracture fixation. Several anatomical studies of the clavicle have been performed in western population in recent years [ 9 12 ]. However, there was no anatomical study of clavicle in Chinese population in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…15,59 The natural variation in clavicle length was taken into consideration in interpreting results. 3,59 Statistics Statistical analysis was performed with IBM SPSS Statistics version 22 (IBM Corp., Armonk, NY, USA). Percentage, frequency distribution, mean, median, and standard deviation were used to describe the characteristics of variables.…”
Section: Patient-oriented Outcomesmentioning
confidence: 99%